Industrial wastewater treatment with engineered nanomaterials for a sustainable environment - Kamali, Mohammadreza (2019)
Quality of the final discharged effluents from industrial activities has been the subject of significant efforts over several decades to improve the performance of the methods applied for their treatment, either by physico-chemical, biological, or a combination of these processes. Among the emerging technologies, the application of various types of engineered nanomaterials (ENMs) has gained a particular attention in recent years. The present thesis aimed to carry out either experimental studies, surveys and critical reviews in order to synthesize the most sustainable nanomaterials for the treatment of recalcitrant pollutants from the content of industrial effluents. In parallel, the sustainability of other biological and physicochemical methods has been critically assessed and the most sustainable treatment methods have been suggested to be adopted by the industries. It was demonstrated in this thesis that the application of Tagguchi approach can considerably aid to control the properties of iron-based nanoscale particles synthesized by a liquidphase reduction process. Working with this system revealed that both the (reductant/Fe3+) ratio, (R), and the Fe3+concentration, [Fe3+], are the parameters that determine critical characteristics including particle crystalline phase composition, crystallinity and surface area although R has been revealed as the most important one. Nano zero valent iron particles with enhanced properties, synthesized by utilization of ultrasonic irradiation, was successfully tested to degrade organic dyes (methylene blue, as a case study) which are dominant in the wastewater from some industries such as textile factories. Recovery of the nanomaterials after being applied for the treatment purposes is also among the most important parameters for the selection and synthesis of the most sustainable nanomaterials for environmental applications. A novel ZnO/Fe3O4 on Bentonite nanocomposite prepared in this thesis showed acceptable photocatalytic decomposition of 2,4 dichlorophenol besides the ability to be recovered after being used. Magnetic nanocomposites were also tested for the degradation of AOXs from pulp and paper mill effluents and showed acceptable performance in such applications. A framework was also developed in this thesis for the sustainability assessment of the best available technologies to deal with industrial effluents, showing the efficiency of biological treatment methods to deal with industrial effluents although having some limitation to deal with phenolic industrial effluents. With a precise acclimatization process, very high efficiency for the biodegradation of phenol with a high degree of resistance to the shock of initial phenol concentration was achieved using activated sludge process. The results of a critical review, as the future outlook of this thesis, indicated the possibility of integration of engineered nanomaterials and also biological treatment with the membrane technologies in order to overcome the existing barriers for the rapid development of membrane technologies for the treatment of industrial effluents.